Analisis faktor-faktor yang mempengaruhi kualitas informasi laporan keuangan pemerintah kota gunungsitoli - Victorinus Laoli (Faculty of Economics and Business Mulawarman University, 2018)
This study aims to determine the factors that affect the quality of information on local government financial statements. Based on Government Regulation no. 71 year 2010, the quality of financial report information of Central and Regional Government must meet qualitative characteristics. Factors studied include quality of human resources, utilization of information technology, and internal control system. Data collection was done by giving 111 questionnaires, which were distributed to respondents who were staffs at the Regional Device Work Unit (SKPD) at the District / Municipal Management Agency / City of Gunungsitoli. Questionnaires distributed to 111 respondents, only successfully collected again with a complete answer obtained 80 respondents. The data obtained were then analyzed using SPSS 20.00. The test results indicate that the utilization of information technology and internal control system have a significant positive effect on the quality of financial report information of Local Government, while the quality of human resources has no effect. The quality of human resources is not significant due to the lack of human resources itself in terms of quality and quantity. Such as the lack of staff accounting education background, unclear job description, and lack of training to ensure the accounting function goes well on Local Government.